Acetylcholinesterase inhibitory activity of sesquiterpenoids isolated from Laggera pterodonta - Li, Jinliang; Li, Fengchao; Wu, Guoxing; Gui, Furong; Li, Hongmei; Xu, Lili; Hao, Xiaojiang; Zhao, Yuhan; Ding, Xiao; Qin, Xiaoping (Frontiers in Plant Science, 2023)
Plant-derived natural products are important resources for pesticide discovery. Recent studies have shown that the potential of various sesquiterpenoids as acetylcholinesterase (AChE) inhibitors. However, few studies have been conducted with eudesmane-type sesquiterpenes with AChE inhibitory effects. Therefore, in this research, we isolated two new sesquiterpenes, laggeranines A (1) and B (2), along with six known eudesmane-type sesquiterpenes (3–8) from Laggera pterodonta, and characterized their structures and the inhibitory effect they exerted on AChE. The results showed that these compounds had certain inhibitory effects on AChE in a dose-dependent manner, of which compound 5 had the best inhibitory effect with IC50 of 437.33 ± 8.33 M. As revealed by the Lineweaver-Burk and Dixon plots, compound 5 was observed to suppress AChE activity reversibly and competitively. Furthermore, all compounds exhibited certain toxicity levels on C. elegans. Meanwhile, these compounds had good ADMET properties. These results are significant for the discovery of new AChE targeting compounds, and also enrich the bioactivity activity repertoire of L. pterodonta.